Optic and Dielectric Properties of Different Amount NiFe2O4 Nanoparticles Loaded Hydrogels: Synthetic Circuits Applications - Okutan, M.; Coskun, R.; Ozturk, M.; Ozsucu, C.; Yalcin, O. (ELECTROCHEMICAL SOC INC, 2018)
Loaded hydrogels with different amount (2.5%, 5.0%, 7.5% and 10.0%) NiFe2O4 nanoparticles have been prepared for elastic optoelectronic devices in nano size via the copolymerization technics. All samples have been characterized by the UV-Vis absorption spectroscopy. The resistance changes were analyzed by calculating from the slope of the current-voltage plots. The optical band gaps of the NiFe2O4 nanoparticles loaded hydrogels decreases with increase of loading of nanoparticles amount. At room temperature (RT), frequency and applied bias voltage dependence of complex impedance, electric modulus, tangent factor and ionic conductivity have been studied with the impedance spectroscopy (IS). In addition, frequency and applied bias voltage of dependence on dielectric properties for NiFe2O4 nanoparticles loaded hydrogels were compared with each other. Frequency evolution of the dielectric properties are drastically effected interface and electrode polarization. The lowest and highest values of the epsilon' and epsilon '' were determined for 10% and 2.5% loaded NiFe(2)O(4)( )nanoparticles depend on applied bias voltage. The complex impedance based Cole-Cole diagrams and their adopted to Smith-Chart have been analyzed for synthetic equivalent resistance-capacitance circuits via frequency. The UV-Vis absorption values decreases and the conductivity values increases with increase because of increasing NiFe2O4 nanoparticles amount and the grain size of loaded hydrogels structure in general. Different amount NiFe2O4 nanoparticles loaded hydrogels will provide great benefits for optoelectronics and non-linear optical applications in the nanotechnology and photovoltaic devices. (C) The Author(s) 2018. Published by ECS.
Keywords: ELECTRIC MODULUS; BROWNIAN-MOTION; CONDUCTIVITY; FREQUENCY; NANOCOMPOSITE; IMPEDANCE; PERMITTIVITY; DISPERSION; VOLTAGE; NANOCRYSTALS; Materials Science; Physics